O trabalho do pediatra: um estudo das tarefas e das dificuldades vivenciadas em um serviço de urgência - Eglea Maria da Cunha Melo (2006)
Medical profession has undergone deep modifications for the past years. Literature gives evidence of an increasing dissatisfaction degree among these professionals, pediatricians included, often times with reflections on their health. The results available in literature provide knowledge of morbidity among doctors, but leave gaps as to the understanding of the work, whose demands and effective production conditions may be associated to the sickening described. The demandthat originated this research refers to the fatigue and exhaustion reported by the pediatricians on duty in the pediatric urgent care of a public service in Belo Horizonte. Purpose To know pediatricians work and to elucidate the characteristics of its performance in urgent care services. Materials and Method The qualitative and empirical investigation was oriented to real work situations and to listening pediatricians, enabling them to talk about their work, the feelings generated in the performance of the task, the difficulties faced, and strategies elaborated in the solution of the problems. The work performed by the 44 pediatricians of the sample,70% of the doctors of the service, was analyzed by means of direct observation, collective interviews and group arrangement. The institution and the workers characteristics were analyzed by means of documental research and statistic data analysis. Seven of these pediatricians were observed at work and six others were gathered in a group to discuss the problems raised. Data organization was made in continuous process, not linear, which allowed the identification of the difficulties experienced by pediatricians while on duty. Results The studied pediatricians aresubject to constraints derived from distinct factors: system organization, notedly the fragility of the reference and counter-reference mechanisms, users aggressiveness, seasonal increase of demand, specially in the months of March, April and May and June, large number of care services considered simple, non recognition for the effort engaged in the work and the need to admit a child due to lack of social, economical and family conditions. It was clear that many of the difficulties are due to thecharacteristics of work at the urgency like: the need of remaining balanced even before stressing situations, the fear of making mistakes and be sued, the feeling of guilty for not having done everything he could. Others concern the difficulty in the performance of the pediatric act like: dealing with a third person to obtain the information, the difficulties of the childs physical examination. Conclusion The quality of the care service given to children in an urgent service is also affected by structural factors. The technical and subjective dimensions of pediatricians activities are influenced by factors extrinsic to the context of the tasks performance. When performing their work in pediatric urgent services, the doctor experiences constraints that may affect his health. The understanding of the work allowed suggesting clues for the transformation of the identified situations.